Determinant of Net Profit Margin in Islamic Bank: Evidence From Indonesia - Sururi, Sururi; Kuntoro, Agus; Dedat Dingkoroci Akasumbawa, Muhammad; Deni Putra, Muhammad (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the factors influencing the Net Profit Margin (NPM) of Islamic banks in Indonesia, focusing on risk aversion (CAP), default risk (NPF), liquidity (FDR), and operational size (SIZE). The research aims to explore how these variables affect profitability in the Indonesian Islamic banking sector. The study uses balanced panel data from Islamic banks over the period 2014–2023 and applies panel regression analysis to examine the relationships between the variables. The findings indicate that risk aversion negatively affects NPM, while liquidity and operational size have a positive influence on NPM. Default risk does not significantly impact NPM. Additionally, the study includes a dummy variable for the COVID-19 pandemic, which shows a negative effect on NPM, reflecting the adverse impact of the pandemic on bank margins. This research contributes to the literature on the determinants of profitability in Islamic banking by providing new insights into how risk aversion, default risk, liquidity, and operational size influence NPM, particularly during periods of economic disruption